HIV and Homosexuality: In the Light of Therapeutic Interventions - Ravinder Yadav; Varinder saini; Sheshna; Ankur (Journal of Human Health Research, 2022)
In this article the author reviews research on high risk factor of Human Immunodeficiency Virus in homosexuals and how lack of awareness & unprotected anal sex contribute substantially to new infections among this population. current HIV prevention efforts by providing insight into the patterns of Indian MSM behavior and sexual partnerships, and the specific cultural, social inequality, the gaps and lack of knowledge and psychological context in which HIV risk is occurring. And the need to develop effective awareness programs for well-functioning prevention of HIV and considerable understanding of the logistical and socio-cultural barriers MSM experience while accessing HIV prevention services. And in last will put light on therapeutic interventions for Human Immunodeficiency Virus, behavioral interventions that are socially and culturally appropriate for the population or community being prioritized and addressing multilevel psychosocial factors, including skills building and strategies to foster self-acceptance and increased social support for MSM. At the same time, prevention messages need to be designed and adapted to the knowledge level and culture of people.
Keywords: HIV